Arterial or venous free flaps for volar tissue defects of the proximal interphalangeal joint: A comparison of surgical outcomes - Choi, Min Suk (Arch Plast Surg, 2020)
BACKGROUND: For volar soft tissue defects of the proximal interphalangeal (PIP) joint, free flaps are technically challenging, but have more esthetic and functional advantages than local or distant flaps. In this study, we compared the long-term surgical outcomes of arterial (hypothenar, thenar, or second toe plantar) and venous free flaps for volar defects of the PIP joint. METHODS: This was a single-center retrospective review of free flap coverage of volar defects between the distal interphalangeal and metacarpophalangeal joint from July 2010 to August 2019. Patients with severe crush injuries (degloving, tendon or bone defects, or comminuted/intra-articular fractures), thumb injuries, multiple-joint and finger injuries, dorsal soft tissue defects, and defects >6 cm in length were excluded from the study, as were those lost to follow-up within 6 months. Thirteen patients received arterial (hypothenar, thenar, or second toe plantar) free flaps and 12 received venous free flaps. Patients’ age, follow-up period, PIP joint active range of motion (ROM), extension lag, grip-strength ratio of the injured to the uninjured hand, and Quick Disabilities of Arm, Shoulder & Hand (QuickDASH) score were compared between the groups. RESULTS: Arterial free flaps showed significantly higher PIP joint active ROM (P=0.043) and lower extension lag (P=0.035) than venous free flaps. The differences in flexion, grip strength, and QuickDASH scores were not statistically significant. CONCLUSIONS: The surgical outcomes of arterial free flaps were superior to those of venous free flaps for volar defects of the PIP joint.